Effect of the state of surface layer on 40х steel fatigue characteristics - Vakulenko, Karyna; Kazak, Iryna; Matsevityi, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2016)
Cyclic testing of 40X structural steel with the implementation of the intermediate surface plastic deformation of the samples by the proposed special technique using the striker-ball tool is described. Changing the level of degradation of the material was determined by the coercive force method. The tests were carried out with the purpose to ascertain the possibility of increasing the durability of the material as the result of the surface treatment by reducing the concentration of accumulated fatigue defects. The test results showed an increase of durability of steel from 3-5 up to 10 times or more (with larger amplitudes), accompanied by a decrease in the values of the coercive force, and the increase in the samples endurance limit by 20-40 MPa. The authors attributed this effect to healing of the material defects occurred as a result of surface treatment, and refinement of the surface layer structure and improving the level of compressive macrostrains on it which was established with the help of the X-ray method. The obtained results indicate the possibility of using this kind of surface treatment to heal defects in products which were in operation and the need to reduce the level of degradation of the metal in order to prolong their life.